Impact of Data Protection Laws on Consumer Trust in E-Commerce in Uganda - Kabumba, David (American Journal of Law, 2024)
Purpose: The aim of the study was to assess the impact of data protection laws on consumer trust in e-commerce in Uganda. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that laws, designed to safeguard personal information, have enhanced transparency and accountability in the way online businesses handle consumer data. Studies indicate that stringent data protection regulations, such as the General Data Protection Regulation (GDPR) in Europe, have led to increased consumer confidence as they assure customers that their personal information is handled with care and used responsibly. Compliance with these laws requires e-commerce businesses to implement robust security measures, thus reducing the risk of data breaches and misuse of personal information. Consequently, consumers feel more secure when sharing their data, which fosters trust and encourages online transactions. Moreover, the requirement for businesses to obtain explicit consent from users before processing their data further empowers consumers, making them more likely to engage in e-commerce activities. Implications to Theory, Practice and Policy: Social exchange theory, information privacy theory and trust transfer theory may be used to anchor future studies on assessing the impact of data protection laws on consumer trust in e-commerce in Uganda. E-commerce platforms can enhance consumer trust by prioritizing transparency and education about data protection practices. Policy recommendations should advocate for global harmonization of data protection standards to simplify compliance for multinational e-commerce businesses and ensure consistent protections for consumers worldwide.